Knowledge partitioning: a strategic approach to product lifecycle management. (4th April 2005) - Therani, Madhusudan; Tanniru, Mohan
The vision of Product Lifecycle Management (PLM) articulates a holistic approach to managing product and service related knowledge in engineering organisations. We characterise PLM as a large-scale knowledge management effort in engineering organisations. Analysis of enterprise information systems suggests that effective utilisation is hindered by ineffective operationalisation, inappropriate contextual reuse and fragmentation of knowledge. Based on case studies, we present a Knowledge Partitioning approach wherein organisational knowledge is classified as data-related, process-related, and control-related. Combining these types of knowledge appropriately may enable effective contextual knowledge reuse. Benefits and issues in adopting such an approach are discussed.